1999
DOI: 10.1002/(sici)1096-9861(19990428)407:1<65::aid-cne5>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Kainate activation of horizontal, bipolar, amacrine, and ganglion cells in the rabbit retina

Abstract: Patterns of excitation in populations of retinal bipolar, amacrine, and ganglion cells were mapped by activating α‐amino‐3‐hydroxyl‐5‐methylisoxazole‐4‐propionic acid (AMPA) and kainate (KA) receptors with KA in the presence of the channel‐permeant guanidinium analogue 1‐amino‐4‐guanidobutane (AGB). Registered serial thin sections were probed with immunoglobulins targeting AGB, glutamate, glycine, and γ‐aminobutyric acid (GABA) to visualize KA‐evoked responses and the neurochemical signatures of distinct cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 66 publications
5
61
0
Order By: Relevance
“…They do for some other cell types. Horizontal cells (Marc et al, 1995;Marc, 1999b) and starburst amacrine cells (Marc, 1999b) can be extracted via their distinctive signatures, and other cell types display strong superclasses; e.g., mammalian cone ONcenter and OFF-center bipolar cells have distinctive signatures (Kalloniatis et al, 1996). This does not prove that all natural classes should have characteristic signatures, even when excitation signals are added to the data.…”
Section: Structural Correlates Of Classesmentioning
confidence: 98%
See 2 more Smart Citations
“…They do for some other cell types. Horizontal cells (Marc et al, 1995;Marc, 1999b) and starburst amacrine cells (Marc, 1999b) can be extracted via their distinctive signatures, and other cell types display strong superclasses; e.g., mammalian cone ONcenter and OFF-center bipolar cells have distinctive signatures (Kalloniatis et al, 1996). This does not prove that all natural classes should have characteristic signatures, even when excitation signals are added to the data.…”
Section: Structural Correlates Of Classesmentioning
confidence: 98%
“…Brace, 1992;Penn et al, 1994;Jacoby et al, 1996;Stafford and Dacey, 1997;Xin and Bloomfield, 1997). Most amacrine cells are GABA immunoreactive, and GABA-immunoreactive dendrites comprise ϳ80% of the mass of the inner plexiform layer (Marc, 1992(Marc, , 1999bMarc et al, 1995Marc et al, , 1998. GABA is a 97 Da molecule and would clearly leak from GABA in amacrine cells (containing ϳ10 mM GABA) through gap junctions at nearly diffusion-limited rates into ganglion cells.…”
Section: Coupling Signaturesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the rabbit retina, kainate responses were recorded from various types of neuronal cells (Marc, 1999). The light responses of most retinal neurons are mediated primarily by AMPA receptors that desensitize to a maintained plateau (Thoreson and Witkovsky, 1999).…”
Section: Functional Relevancementioning
confidence: 99%
“…19,20 Previous experiments have shown that only calcium blockers prevented agmatine from entering synaptosomes. 21 Although other channels may be involved in different cell membrane locations, it is highly likely that calcium or nonspecific cation channels are responsible for the uptake of agmatine in our experiments.…”
Section: Discussionmentioning
confidence: 99%